Perfect, thanks.
One last thing: do I have to write like this "f o g (x)" when = f(g(x)) or just "f o g" is acceptable?
I mean: "f(g(x)) = f o g" or "f(g(x)) = f o g (x)" ? or it doesn't matter?
Hi This post has helped me with my problem, but I am still confused on the part that says
if we explicity calculate f(g(x,y)), we get f(g(x,y)) = (y-2, -x).
so if (x,y) = (y-2,-x) we get 2 equations in x and y. can you solve these?
How do you find y-2, and -x, I just cant see how you got to these.
Please help I have nearly no hair left!!